THE EFFECTIVENESS OF SISKEUDES IN FINANCIAL MANAGEMENT IN GELANG VILLAGE, TULANGAN, SIDOARJO - Syarifah, Sabrina Rif’aus; Agustina , Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines the effectiveness of the Village Financial System (Siskeudes) in supporting village financial management. This study focuses on the achievement of indicators of transparency, accountability, and user satisfaction, as well as the achievement of overall program objectives. Method: This study uses a qualitative descriptive approach with data collection techniques through observation, documentation, and interviews. Results: The results show that the implementation of Siskeudes has succeeded in improving the transparency of information and the quality of village financial reports, which has contributed to the success of the program. Thanks to more accurate and accountable reports produced by village staff, the objectives of transparency and accountability have been largely achieved. Satisfaction with the program is also quite high, indicating that officials feel supported and the community feels there is greater transparency. Despite facing challenges related to operator skills and internet connectivity, Siskeudes has succeeded in speeding up the recording process and improving administrative order. Siskeudes has helped villages achieve transparent, accountable, and orderly financial management, although improvements are still needed in human resource capacity and infrastructure. This indicates the overall level of achievement of the objectives. Since most of the program objectives have been achieved, the implementation of Siskeudes can be considered effective overall. These results are in line with Campbell's (1989) theory, which states that the extent to which organizational goals can be achieved is consistent and repetitive. Novelty: The abstract does not explicitly state a separate novelty or contribution section, but the implied novelty is the confirmation of the effectiveness of Siskeudes in achieving transparency, accountability, and user satisfaction through empirical findings and linking the results to Campbell's (1989) theory regarding the consistent and repetitive achievement of organizational goals.